89 IMPLANTATION OF A FIBROBLAST PATCH IMPROVES LEFT VENTRICULAR SYSTOLIC FUNCTION AND PREVENTS REMODELING AFTER MYOCARDIAL INFARCTION. (1st January 2006) - Thai, H.; Juneman, E.; Castellano, L.; Do, R.; Gaballa, M.; Goldman, S.
Abstract : Background: Tissue engineering is a novel method to restore myocardial function in ischemic heart disease. One technique is to apply a biologically active graft onto the infarcted region (IR) of the left ventricle (LV). The effects of a fibroblast patch (3DFC) placement on the IR of the LV on systolic/diastolic function in a coronary artery ligation (CAL) model of heart failure were evaluated. Methods: CAL to induce myocardial infarction (MI) is performed on Sprague-Dawley rats. The 3DFC patch is placed on the IR. Echos were done at 3 weeks. Hemodynamics was measured. LV regional systolic displacement (SD), LV ejection fraction (LVEF), LV fractional shortening (FS), and LV pressure/diameter relaxation curves were obtained. Results: 3DFC patch placement improved ( p < .05) LV SD, LVEF, and LVFS in MI animals. The LV diastolic relaxation slope and the LV diameter of the MI animals that received a patch are comparable to the sham rats. Summary: Implantation of a fibroblast mesh on the IR of the LV improved LV systolic function. The patch also prevented LV dilation and normalized LV diastolic function post MI. Our data illustrate the future potential of using a biologically active graft in the treatment of ischemic heart failure.